Competitive potential of ad ministrative-territorial units: assessment and development directions - Maxim B. Ivanov (Vestnik of Vitebsk State Technological University)
The modern socio-economic development of Belarus takes place in the context of increasing competition between its administrative-territorial units (hereinafter referred to as ATUs) for economic and demographic resources through improving the population's standard of living. Experience shows that the development of competitive advantages and an efficient economy is necessary for the sustainable development of regions, especially in small towns and rural areas. The aim of this research is to develop theoretical and methodological principles and practical recommendations for enhancing the competitive potential of the ATUs of the Republic of Belarus. The article highlights both general and specific problems related to the formation of competitive potential for certain ATUs in the Brest region. Based on the author's proposed methodology for comprehensive assessment of competitive potential, a grouping of the ATUs was conducted. The assessment is based on an index method that utilizes indicators reflecting the competitive opportunities based on available resources and the effectiveness of their utilization.